Kininogen-Nitric Oxide Signaling at Nearby Nonexcited Acupoints after Long-Term Stimulation - Ting Wang; Geng Zhu; Liyue Qin; Qian Wang; Chen She; Dongsheng Xu; Weiwei Hu; Kenghuo Luo; Ying Lei; Yanling Gong; Arijit Ghosh; Dongni Ma; et al. (Elsevier, 2021)
Acupuncture treatment is based on acupoint stimulation; however, the biological basis is not understood. We stimulated one acupoint with catgut embedding for 8 weeks and then used isobaric tags for relative and absolute quantitation to screen proteins with altered expression in adjacent acupoints of Sprague Dawley rats. We found that kininogen expression was significantly upregulated in the stimulated and the nonstimulated adjacent acupoints along the same meridian. The enhanced kininogen expression was meridian dependent and was most apparent among small vessels in the subcutaneous layer. Enhanced signals of nitric oxide synthases, cGMP-dependent protein kinase, and myosin light chain were also observed at the nonstimulated adjacent acupoints along the same meridian. These findings uncover biological changes at acupoints and suggest the critical role of the kininogen-nitric oxide signaling pathway in acupoint activation.